Retinal vessel oximetry-calibration, compensation for vessel diameter and fundus pigmentation, and reproducibility - Hammer, Martin; Vilser, Walthard; Riemer, Thomas; Schweitzer, Dietrich (Journal of biomedical optics, 2008)
The purpose of this study was to measure the hemoglobin oxygenation in retinal vessels and to evaluate the sensitivity and reproducibility of the measurement. Using a fundus camera equipped with a special dual wavelength transmission filter and a color charge-coupled device camera, two monochromatic fundus images at 548 and 610 nm were recorded simultaneously. The optical densities of retinal vessels for both wavelengths and their ratio, which is known to be proportional to the oxygen saturation, were calculated. From 50-deg images, the used semiautomatic vessel recognition and tracking algorithm recognized and measured vessels of 100 microm or more in diameter. On average, arterial and venous oxygen saturations were measured at 98+/-10.1% and 65+/-11.7%, respectively. For measurements in the same vessel segments from the five images per subject, standard deviations of 2.52% and 3.25% oxygen saturation were found in arteries and veins, respectively. Respiration of 100% oxygen increased the mean arterial and venous oxygen saturation by 2% and 7% respectively. A simple system for noninvasive optical oximetry, consisting of a special filter in a fundus camera and software, was introduced. It is able to measure the oxygen saturation in retinal branch vessels with reproducibility and sensitivity suitable for clinical investigations.